Área de preservação permanente em zona urbana e regularização da moradia - Pacheco, Juliana Muniz (2013)
The present research was based in discussions which took place when Forestry Code of 1965 took force, a time when the thesis of permanent preservation areas in cities was not anywhere peaceful. Within this background, it was pursued the historic institute source of this environmentally sensitive areas, as well as its fundamental (or ratio legis), nowadays denominated environmental or ecological function. Using such concepts as base ground (delataria ground), the study has progressed towards Urban Planning Law and its relationship with environmental regulation, an updated discussion with needed confrontation before the persistent thesis of excluding one legal order in place of another. For this purpose, it was addressed the constitutional competences array (delataria array) and the sustainable development principle. From the urban planning perspective, it was prioritized focus in Housing Ownership and its regularization, most sensitive point regarding harm to ecologically balanced environment and demand generator towards human being dignity. During the research development, Law nº 12.651, from 25th May, 2012 stood out, with its subsequent modification, reflecting in the premises, guidelines and final conclusions of the present dissertation, in a way that housing regularization achieved a new approach both for the law and research followed. In this way, one may conclude that the Public Power, in the role of managing a balanced environment, won more adequate procedures to achieve Housing Ownership, through landing regularization and not only environmental balance but life quality, security and health of the involved population